PHYTOCHEMICAL COMPOSITION, IN VITRO ANTIOXIDANT AND CYTOTOXIC ACTIVITIES OF SEEDS OF CONVOLVULUS ARVENSIS LINN. - TAGHREED A. IBRAHIM; ATEF A. EL-HELA; NEVEIN M. ABD ELHADY; NABIL M. ABO-ELFETOH (International Journal of Pharma and Bio Sciences, 2016)
In vitro antioxidant and cytotoxic activities of methanol extract of the seeds of Convolvulus arvensis Linn. and its successive fractions; chloroform, ethyl acetate and n-butanol were evaluated. Total phenolics and flavonoid contents of methanol extract and ethyl acetate fraction were estimated. The highest antioxidant activity was achieved in ethyl acetate fraction (120.3±0.55 mg GAE) followed by methanol extract (84.8±0.62 mg GAE). The ethyl acetate fraction showed the strongest DPPH and nitric oxide free radical scavenging activities (IC50 28.16±0.45 and 51.92±1.45 for DPPH and nitric acid, respectively). Ethyl acetate fraction showed the highest cytotoxic effect against Hela cell line (IC50 17.33±0.58). From ethyl acetate fraction seven compounds were isolated and identified; gallic acid (1), ferulic acid (2), chlorogenic acid (3), quercetin (4), apigenin-7-O-glucoside (5), quercetin-7-O-rhamnoside (6) and quercetin-3-O-rutinoside (7) using different spectroscopic techniques. Therefore, methanolic extract and the ethyl acetate fraction of the seeds of Convolvulus arvensis are recommended to be used as natural antioxidant and cytotoxic agents.